Effects of High-Intensity Interval Training on glycemic control and body composition of individuals with Type 2 Diabetes mellitus: An integrative literature review (Research, Society and Development, 2023)
Type 2 Diabetes Mellitus (DM2) is characterized by resistance and inadequate production of insulin by the pancreas, and is associated with factors such as obesity and a sedentary lifestyle. The treatment involves changes in lifestyle, such as exercise, and, in some cases, the use of medication, and continuous control is required. In this sense, High Intensity Interval Training (HIIT) is a promising alternative physical treatment. This study aims to investigate the effects of HIIT on glycemic control and body composition of individuals with DM2. This is a descriptive literature review, in which randomized controlled trials were included, available for reading in full, published between 2013 and 2023 in English and Portuguese languages, with methodological quality evaluated according to the PEDro Scale. The review included a total of 86 participants, with the number ranging from 16 to 37 in each study. The percentage of participants by gender was not balanced (M=60; F=26). HIIT sessions lasting 11-12 weeks were conducted. Exercise intensity was controlled using different measures, such as maximum heart rate and peak work rate. The analysis of the adjacent literature confirmed the effectiveness of HIIT for DM2 in the parameters addressed, despite some divergence. Improvement was also observed in other measures such as fitness and cardiovascular risk. However, the lack of standardization in training protocols makes future research necessary to provide more solid and detailed evidence on the effects of HIIT in this population.